THE CONNECTION BETWEEN ECOLOGY AND SUSTAINABLE DEVELOPMENT - Shulyak, Daryna; Martynyuk, Svyatoslav; Nurulayev, Shamil; Timchenko, Elizaveta; Kalantaevskyi, Volodymyr; Garkavyi, Valerii (European Science, 2024)
The nature of the modern ecological situation is considered, the emergence and development of the concept of sustainable development is analyzed. The characteristics and principles of sustainable development are studied. It is noted that man changes the e